Supporting the “forgotten” ventricle: The evolution of percutaneous RVADs - James, Les; Smith, Deane E. (Frontiers in Cardiovascular Medicine, 2023)
Right ventricular failure can occur as the result of an acute or chronic disease process and is a challenging clinical condition for surgeons and interventionalists to treat. Right ventricular failure occurs in approximately 0.1% of patients after cardiac surgery, in 2-3% of patients following heart transplantation, and in up to 20-30% of patients after LVAD implantation. Regardless of the cause, right ventricular failure portends high morbidity and mortality and is associated with longer hospital stays and higher healthcare costs. The mainstays of traditional therapy for severe right ventricular failure have included pharmacological support, such as inotropes and vasopressors, and surgical right ventricular assist devices. However, in recent years catheter-based mechanical circulatory support strategies have offered novel solutions for addressing right ventricular failure without the morbidity of open surgery. This manuscript will review the pathophysiology of right ventricular failure and the evolution of techniques for supporting the right ventricle, with a focus on various institutional experiences with minimally invasive right ventricular assist devices.